Heat-strengthenable borosilicate glass

JP7629299B2Active Publication Date: 2025-02-13SCHOTT AG
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020209226
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-17
Publication Date
2025-02-13
Estimated Expiration
2040-12-17

Smart Images

  • Figure 0007629299000001
    Figure 0007629299000001
  • Figure 0007629299000002
    Figure 0007629299000002
  • Figure 0007629299000003
    Figure 0007629299000003
Patent Text Reader

Abstract

To provide a glass whose parameters which can be influenced by a material during thermal tempering are optimized.SOLUTION: This object is achieved through an appropriate combination of stoichiometric glasses, i.e. glasses that also exist in the same stoichiometry as crystals and can be assumed that the stoichiometric glasses have properties very similar to each of glass and crystal due to the identical topology of the assemblies. More specifically, there is provided a glass having a high modulus of elasticity, a desired coefficient of thermal expansion below the glass transition range and a high coefficient of thermal expansion above the glass transition range and desired values for the upper cooling point and the processing point, as a borosilicate glass which have optimal thermal temperability and can be used as thermally tempered, high-strength flat glass products for safety glazing, among other things, in construction, for vehicle glazing and for applications in the home tech sector.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to borosilicate glasses, in particular glass sheets, which have optimal heat strengthening properties and can be used as heat strengthened high strength glass sheets products, in particular for applications in the building industry, safety glazing, vehicle glazing, and home tech sectors.

[0002] In particular, the glasses are characterized by having a high modulus of elasticity, a desired coefficient of thermal expansion below the glass transition range and a high coefficient of thermal expansion above the glass transition range, as well as desired values ​​of the annealing point and the working point.

[0003] Prior Art Increasing the fracture strength of glass by thermal tempering has been a long-standing technique, and much work exists on the theory of thermal tempering and the calculation of the resulting stress profiles. Here are some examples: Gardon, R.: Calculation of temperature distribution in glass plates undergoing heat treatment J. Am. Ceramic. Soc. 41 (1958), pp. 200-209, Blank, K.: Thermisch vorgespanntes Glas Teil 1, Glastechnische Berichte 52 (1979), p. 1-13, Oel, HJ u,a,: Thermisches Vorspannen von Glasscheiben, Glastechnische Berichte 57 (1984), pp.1-6, Hennig, M., Wiltzsch, S.: Thermisches Haerten duenner Kalk-Natron-Flachglaeser, HVG- Mitteilung Nr. 2137 (2008), Bach, H., Neuroth, N.: The Properties of Optical Glass, Strengthening of Glass, Springer Verlag 1998, pp. 196-200.

[0004] Thermally strengthened glass is needed for many applications, especially in the safety glass sector, where special requirements are placed on the properties of safety glass plus fire resistance properties.

[0005] Regular untempered soda lime glass plates will explode in a short time even if they are only exposed to heat for a short time. If large pieces of glass fall, they can spread the fire to the next room. For this reason, attempts have been made to prevent the glass plates from breaking by inserting wire mesh (wired glass).

[0006] Fire-resistant glass must meet the requirements for fire resistance classes G and F (according to DIN 4102 Part 13 / ISO 834 or fire resistance classes E, EW and EI according to EN 13501). In this case, the glazing including the frame and supports must prevent the passage of flame and fire gases for at least 30, 60, 90 or 120 minutes according to the standard temperature-time curve (ETK) in order to be classified as G30, G60, G90 or G120.

[0007] Similar rules apply to classes F30, F60, F90 and F120, where the glass on the side facing away from the fire must not heat up, on average, by more than 140°C above its initial temperature.

[0008] Additional requirements are often imposed on architectural glazing. For example, door glazing must ensure safe passage in addition to fire resistance. The glazing must not only meet fire resistance standards, but also safety standards, such as ESG (DIN 1249 Part 12 or DIN EN 12150) for single-glazed safety glass.

[0009] The ESG requirements according to DIN EN 12150 are: A flexural tensile strength of at least 120 MPa, with the strength enhancement caused by surface compressive stresses. · If a sheet of glass breaks, it must shatter into many, many small pieces. 50×50mm 2 For an area of ​​1.0 mm and a glass thickness of 4 to 12 mm, the minimum number of fragments is 40.

[0010] Products based on thermally strengthened soda-lime flat glass are used, for example, in the building industry as ESG, as vehicle glazing and as glass covers for PV modules, however their use as fire-resistant glazing is only possible in a limited way and must be explicitly verified.

[0011] Thermally strengthened soda-lime glass in the thickness range of 6-15 mm can achieve a fire resistance time of 30-60 minutes. The disadvantage of these glasses is that during temperature loading according to the standard temperature-time curve (ETK), the softening temperature is exceeded early, which can lead to a transition to a viscous plastic state, leading to deformation and subsequent slipping out of the frame. The main reason for this is that the softening temperature (EW; i.e., 10 7.6 The reason is that the plate thickness (temperature in dPas) is too low, about 720 °C. Other influencing factors are the plate size, the plate thickness, the width of the edge cover, the plate grip and the nature of the frame material. The wider the plate edge cover, the longer the glass plate is prevented from slipping off from the edge area when the glass reaches its softening temperature during the fire load process.

[0012] At the same time, however, the width of the covered edge area is generally limited by the so-called CTE 20 / 300 The glass transition temperature (CTE) is measured as Glas ) together with the coefficient of linear thermal expansion of the glass at lower temperatures, determine the level of stresses that occur during the fire load between the hot free-standing plate center and the cold covered plate edges. If this stress exceeds the strength of the glass during a fire, it will inevitably lead to the glass plate cracking and thus to a complete loss of fire resistance. For this reason, it is not possible to select edge covers for plates of any size in order to achieve the highest possible fire resistance time.

[0013] Also, attempts have already been made to develop multi-layer laminated glass systems to increase the fire resistance time of soda-lime glass. In this connection, several soda-lime glass plates, some of which have been thermally strengthened, are bonded together with a heat-absorbing layer between them. However, this type of laminated glass has the disadvantage that it must have several glass layers and heat-absorbing layers to achieve a higher fire resistance rating. These systems are thick and heavy, which makes the installation and framing complicated and expensive.

[0014] Approximately 9×10 -6 K -1 CTE Glas In addition to soda-lime glass, which has a hardness of 3.0 to 5.0 × 10, industrial specialty glasses are also heat-strengthened. -6 K -1 Low CTE Glas value, which on the one hand prevents the additional thermal stresses occurring in the event of a fire from becoming too great. However, this is also, on the other hand, opposed to thermal strengthening: see in particular Werner Kiefer, Thermisches Vorspannen von Glaesern niedriger Waermeausdehnung, Glastechnische Berichte 57 (1984), No. 9, pp. 221-228, where the thermal strengthening process of glass plates (heating to a temperature, e.g. 100 K above the annealing point, shock cooling by blowing, etc.) is described in detail.

[0015] According to Kiefer, cited above, the thermal strengthening σ of a glass plate is given by:

number

[0016] where E is the elastic modulus, μ is the Poisson's ratio, and ΔT is the difference between the surface temperature and the center temperature of the plate when the center temperature of the plate passes the annealing point during shock cooling. According to Kiefer, cited above, the following applies to ΔT:

number

[0017] where h is the heat transfer coefficient between the plate and the cooling medium, e.g., blown air, d is the thickness of the plate, κ is the thermal conductivity of the glass, T ambient is the temperature of the cooling medium.

[0018] T G is the stress T GHigher and more mitigated, T G It is a discretization of the glass transition region in the sense that below it there is no longer any relaxation. Strictly speaking, this temperature depends on the cooling rate. The best estimate that is independent of the cooling rate is the annealing point. Therefore, in this disclosure, T G is identified as the annealing point OK.

[0019] For example, in the above cited references by Kiefer et al., the glass transition temperature is often used instead of the above discretization. This is not 100% correct, since the glass transition temperature is related to structural relaxation, not stress relaxation. However, this is because (T G -T ambient ) and (OK-T ambient ) are almost the same, the difference between the annealing point and the glass transition temperature is small, so there is little effect.

[0020] According to (1), α Glas The upper limit of E, μ, κ, and T clearly imposes a severe restriction on the thermal toughening ability. G For a fixed value of h, we move further to the thickness of the plate, i.e., CTE Glas Despite this upper limit, if it is desired to achieve a certain strengthening, the thickness of the plate must not fall below a certain value, which has the undesirable consequence of increasing the weight of the glass.

[0021] Efforts are being made to maximize the heat transfer coefficient h, in particular by choosing water with an oil layer as the cooling medium (see Kiefer cited above), which leads to undesirable fire risks. With regard to air blowing, the technical possibilities have been exhausted (impinging stream from a nozzle field): see Carl Kramer, Alfred Muehlbauer, Praxishandbuch Thermoprozess-Technik, Bd. 1, Vulkan Verlag, Essen (2002).

[0022] For the reasons stated above, no borosilicate glasses are currently known which can be used simultaneously as safety glass and for fire resistance purposes G120 to G180 and which are able to achieve the prestress required for safety glass on conventional air prestressing devices with plate thicknesses of less than 6 mm.

[0023] This is also true when considering effects that contribute to strengthening, not mentioned in Kiefer cited above. Due to the different cooling rates at the plate surface (fast due to direct contact with the cooling medium) and at the center (relatively slower due to low heat conduction from the center to the surface), the fictive temperature of the glass at the center is lower than at the surface. This is associated with a relative contraction of the center with respect to the surface, which leads to improved strengthening. This effect is described in detail in F. Mauch, J. Jaeckle, Thermoviscoelastic theory of freezing of stress and strain in a symmetrically cooled infinite glass plate, Journal of Non-Crystalline Solids 170 (1994) 73-86. The important parameter for this effect is the CTE Glas For a fixed value of , the glass transition region CTE liquid The value of thermal expansion at higher temperatures is preferably as high as possible.

[0024] It should also be noted that, with regard to the preferred use of borosilicate glasses, it is recommended to heat the glass as far as possible above the annealing point in order to achieve the highest possible tempering: see Kurt Blank, Thermisch vorgespanntes Glas, Glastechnische Berichte 52 (1979), Part 1: pp 1-13, Part 2: pp 51-54. In order to be able to handle the glass even at such high temperatures, it is desirable that the viscosity of the glass does not decrease too much with increasing temperature. So-called "long" glasses, whose working point is as high as possible above the annealing point, are therefore preferred. This is generally the case for borosilicate glasses, which suggests that the problem of the invention described below should be restricted to the family of borosilicate glasses.

[0025] Problems to be Solved by the Invention In the prior art, there is no borosilicate glass that can be processed into fire-resistant safety glass with a plate thickness of less than 6 mm. The problem of the present invention is to provide a glass in which the parameters that can be influenced by the material during tempering are optimally dimensioned. In particular, the elastic modulus, the annealing point, the working point and the coefficient of thermal expansion above the glass transition region are all preferably selected to be relatively high, taking into account tempering. Furthermore, the density should not exceed a desired value, taking into account the weight of the subsequent glass product. It is also desirable that the glass can be manufactured by modern flat glass float or drawing processes.

[0026] This problem is solved by the subject matter of the claims.

[0027] Detailed Description of the Invention The problem is solved by a suitable combination of stoichiometric glasses, i.e. glasses that also exist as crystals in the same stoichiometry and that, due to the identical topology of the aggregates (as investigated in many examples in the literature, for example by NMR measurements), can be assumed to have very similar properties, respectively as glasses and as crystals. For this purpose, stoichiometric glasses are selected whose mixtures allow the behavior according to the solution of the problem according to the invention to be realized. In the present application, these stoichiometric glasses are also called "base glasses" or "constituent phases".

[0028] Describing glasses based on the constituent phases that are assigned to them is not a new concept: by specifying a base glass, conclusions can be drawn about the chemical structure of the glass (see Conradt R: “Chemical structure, medium range order, and crystalline reference state of multicomponent oxide liquids and glass“, in Journal of Non-Crystalline Solids, Volumes 345-346, 15 October 2004, pp 16-23).

[0029] The present invention relates to the following glass constituent phases: [Table 1] wherein the sum of the proportions of anorthite and diopside is in the range of 1 to 30 mol %.

[0030] Furthermore, the glasses according to the invention should preferably satisfy the further conditions which are formally related to the composition of the constituent phases given below.

[0031] First, we give a conversion matrix for mutual conversion between the composition data of simple oxides and the composition data of constituent phases.

[0032] Conversion of constituent phase compositions to simple oxide compositions and vice versa The composition of the constituent phases is given by the following normalized formula for conversion: [Table 2]

[0033] These compositions can be calculated using the matrix described here for the following simple oxides: [Table 3] where the composition data in mole percent for the base glass is multiplied from the right into the matrix as a column vector: [Table 4]

[0034] The result of multiplying the column vector by the matrix is ​​the composition of the glass in mole percent.

[0035] Conversely, the compositions in mole percent can be easily converted to base glass compositions via the respective inverse matrices, where it should be understood that only base glass compositions that do not give negative values ​​for the base glass when converted are considered according to the invention.

[0036] Importance of the constituent phase and its selection in view of the object of the present invention The composition is selected taking into account the glass constituent phases within the ranges described herein. It is self-evident that the glass constituent phases are amorphous, not crystalline, in the glass product. However, this does not mean that the constituent phases in the amorphous state have an assembly that is completely different from the constituent phases in the crystalline state. As mentioned above, the topology of the assembly, i.e., the interatomic distances resulting from, for example, the coordination of the involved cations with the surrounding oxygen atoms, or the coordination and strength of the bonds between these cations and the surrounding oxygen atoms, are comparable. Therefore, many properties of the glass of the present invention can be fully explained on the basis of the constituent phases (see Conradt R. cited above), in particular to show the achievements of the invention and the problems overcome by the invention. Here, it is to be understood that the glass can be produced not only by using suitable crystals, but also by using normal glass raw materials, as long as it is possible to form the appropriate assembly of the base glass only in stoichiometric ratios.

[0037] The initial choice of alkali and alkaline earth metal tectosilicates as constituent phases was made because, in view of their structure as "packed frameworks", a high elastic modulus and thermal expansion above the glass transition region could be expected. These are reedmergnerite, its potassium analogue, cordierite and anorthite. In view of the required low coefficient of expansion, pure SiO2 is added as a constituent phase. All these phases have different "lengths", i.e., different distances between the working point and the annealing point as glasses, so that the desired profile of viscosity above the annealing point can be produced by the combination of these phases. To introduce an additional degree of freedom, diopside, which is rather "short" as a glass, i.e., has a short distance between the working point and the annealing point, is introduced as a further phase.

[0038] Both of these phases have high annealing points as glasses, which in principle is desirable for thermal strengthening. However, if the annealing points are too high, the initial heating temperature during thermal strengthening would be too high and would not be compatible with the technical boundary conditions of the prestressing device. With this in mind, pure B2O3 is added as a constituent phase.

[0039] Below, calculation methods are given on how to calculate the above-mentioned reference parameters, the elastic modulus, the thermal expansion below the glass transition region and above the glass transition region, the working point and the annealing point, and the density, from the composition of the given constituent phases. These calculation methods are important for selecting the composition of the glass according to the invention from these constituent phases.

[0040] Thermal expansion coefficient below the glass transition region Surprisingly, the location of the thermal expansion coefficient in the target range can be shown using very simple calculation rules, which are derived from the average bond strength.

[0041] It is known from the literature that the thermal expansion coefficient, for example for metals, is inversely proportional to the bond energy (or "depth of the interatomic potential well"): see for example H. Foell, Skript zur Vorlesung "Einfuehrung in die Materialwissenschaft I", Christian Albrechts-Universitaet Kiel, pp. 79 - 83.

[0042] In a simple image of oxide glasses, the cations are each placed in a potential well formed by the surrounding oxygen atoms, and the depth of the potential well is assumed to be the sum of the bond strengths of the various single bonds to the surrounding oxygen atoms, i.e. concentrating the entire interaction energy in the potential well with the central cation and the surrounding oxygen atoms. The reverse case is therefore no longer necessary to consider. The analysis is made more difficult because the oxygen atom may also be located between several different types of cations, which does not happen in purely oxide glasses on the other hand. These values ​​are summarized, for example, in DE 10 2014 119 594 A1.

[0043] [Table 5]

[0044] Given the composition of the glass from the constituent phases listed above, the number of different cations in each phase, and the potential well depths per cation tabulated above, the average potential well depth can be calculated:

number

[0045] In the formula, m is the number of occurrences of the cation type, E pot,j is the potential well depth for the jth cation type, as summarized in the table above, z j,i is the number of jth type of cation in the ith constituent phase. The sums over j are summarized in the table below: [Table 6]

[0046] This average bond strength is inversely related to the thermal expansion coefficient, as is also the case for metals, for example (see H. Foell, cited above). Evaluating a series of different silicate glasses (soda-lime, borosilicate, aluminosilicate glasses) leads to the following formula:

number

[0047] Thus, the CTE Glas can be predicted with an average accuracy of 0.3 ppm / K.

[0048] Taking into account the thermal strengthening, the CTE was calculated according to Eq. (4). Glas is preferably at least 3.8 ppm / K, more preferably at least 3.9 ppm / K, more preferably at least 4 ppm / K, and even more preferably at least 4.1 ppm / K. Taking into account the use as fire-resistant glass, the calculated CTE Glas Preferably, the CTE calculated according to equation (4) is not to exceed 4.8 ppm / K, more preferably not to exceed 4.7 ppm / K, 4.6 ppm / K, or 4.5 ppm / K. Glas is in the range of 3.8 to 4.8 ppm / K, more preferably 3.9 to 4.7 ppm / K, still more preferably 4.0 to 4.6 ppm / K, and still more preferably 4.1 to 4.5 ppm / K.

[0049] Density, Molar Volume and Packing Density Surprisingly, the molar masses M i and density ρ i From this we can very easily calculate the density by the lever rule:

number

[0050] In the formula (5), the numerator is the molar mass, and the denominator is the molar volume of the glass, V molThus, the densities of the glass systems listed here can be predicted with an average accuracy of 1%.

[0051] Density values ​​are given in OV Mazurin, MV Streltsina, TP Shvaiko-Shvaikovskaya, Handbook of Glass Data AC, Elsevier, Amsterdam, 1983-1987.

[0052] From the molar volumes, the packing density χ of the glass is calculated separately as an intermediate parameter for further calculations. For this, the (molar) ion content of each constituent phase is calculated. This means the volume that an ion occupies in one mole of the constituent phase (or more precisely, in one mole of the constituent phase normalized to a simple oxide), if understood as a spherical ion, which Robert Shannon called the "crystal radius": see Robert D. Shannon, Revised Effective Ionic Radii and Systematic Studies of Interatomic Distances in Halides and Chalcogenides, Acta Cryst. A32 (1976), pp. 751-767. These radii vary depending on the coordination number. For the cations, the necessary coordination numbers are taken from the mineralogy literature listed below, in the discussion of the constituent phases. According to Conradt R. cited above, we assume that the coordination number of the cations in the glass is equal to the coordination number of the corresponding crystalline phase. The cations are assigned oxygen atoms according to their valence, e.g., 1 / 2 oxygen ions for 1 sodium ion. The individual oxygen ions are then assumed to be coordinated according to this assignment, i.e., the oxygen ion assigned to the silicon ion is doubly coordinated, etc. In the absence of explicit radius values ​​for the individual coordination numbers in the Robert D. Shannon table cited above, interpolation or extrapolation is performed.

[0053] The resulting molar ionic volumes are tabulated below along with the molar mass and density values.

[0054] [Table 7]

[0055] Thus, the packing density is given by:

number

[0056] For weight considerations, the density is preferably at most 2.45 g / cm 3 , and more preferably at most 2.4 g / cm 3 , and more preferably at most 2.35 g / cm 3 Preferably, the density calculated according to formula (5) is 2.25 to 2.45 g / cm 3 , more preferably 2.3 to 2.4 g / cm 3 , more preferably 2.31 to 2.39 g / cm 3 For example, the density calculated according to formula (5) is at least 2.25 g / cm 3 , at least 2.3 g / cm 3 , or at least 2.31 g / cm 3 For example, the density calculated according to formula (5) may be at most 2.45 g / cm 3 , maximum 2.4g / cm 3 , maximum 2.39g / cm 3 , or at most 2.35 g / cm 3 The range of packing density can be determined by the CTE liquid This is indirectly obtained from the range of calculated values ​​of

[0057] Elasticity The starting point for the calculation of the elastic modulus is the theory of Makishima and Mackenzie: see “Direct calculation of Young's modulus of glass”, “Calculation of bulk modulus, shear modulus and Poisson's ratio of glass”, J. Non-Crystall. Sol., 1973 and 1975. According to this theory, the elastic modulus can be expressed as:

number

[0058] In the formula, e diss.,i is the dissociation energy density (dimension, e.g., kJ / cm) of the i-th component 3 ), and c i is the mole fraction. χ is the packing density.

[0059] For further calculations, we rewrite this as:

number

[0060] Makishima and Mackenzie understand the dissociation energy to be the same as the bond strength above. Having assigned bond strengths to the cations above, we can determine the average value of the molar dissociation energy by multiplying the average potential well depth of the cations above by the number of cations per mole, z, when referring to simple oxides as components:

number

[0061] Thus, we obtain:

number

[0062] The above theory gives very good results for glasses in which the boroxol ring does not occur, but the ad hoc extension to borates carried out by Makishima and Mackenzie is insufficient.

[0063] A new theory by Plucinski and Zwanziger ("Topological constraints and the Makishima-Mackenzie model", J. Non-Crystall. Sol., 2015) supplements the sign notation with a topological prefactor, but the published formula is only suitable for purely covalent glasses (chalcogenides).

[0064] Therefore, a modified topological prefactor is defined here.

[0065] The essence of topological considerations is to count the number of constraints imposed on an atom by bonds to neighboring atoms, as described in detail, for example, in DE 102014119594 A1. These constraints relate, on the one hand, to interatomic distances ("distance constraints") and, on the other hand, to bond angles ("angle constraints"). If an atom has r neighbors (r=coordination number), then the r distance constraints on these neighbors result in r / 2 distance constraints to be assigned to these atoms if the distance constraints are distributed equally between the two bond partners. The bond angles between these neighbors result in a further 2r-3 angle constraints to be assigned to this atom, with the considered atoms at the vertices of the respective angles.

[0066] DE 102014119594 A1 describes a method in which, when calculating the distance and angle constraints, all conditions are weighted by the single bond strength and then additionally weighted again by the respective covalency of the angle constraints (only those resulting from oxygen-cation-oxygen angles: constraints belonging to cation-oxygen-cation angles are ignored). Here, the weighting coefficients are normalized by dividing by the single bond strength or the covalency of the silicon-oxygen bond, respectively, resulting in a number of distance constraints (rounded) of 1.333333333 (i.e. 4 / 3) and angle constraints (rounded) of 1.666666667 (i.e. 5 / 3) per atom for quartz glass. This corresponds to a direct analysis of the topology of quartz glass if, as described in DE 102014119594 A1, one simply counts all distance and angle constraints and ignores the angle constraints of silicon-oxygen-silicon angles.

[0067] Thus, silica glass has a constraint number of "3" per atom, which corresponds exactly to the number of degrees of freedom per atom. In other words, silica glass has no (or in reality, very small) number of degrees of freedom per atom, which explains the small c of silica glass in the differential calorimetry glass transition. p Corresponding jump: See R. Bruening, "On the glass transition in vitreous silica by differential thermal analysis measurements", Journal of Non-Crystalline Solids 330 (2003) 13-22.

[0068] For other oxide glasses, generally lower values ​​of (rounded) 1.333333333 (4 / 3) and 1.666666667 (5 / 3) are given for the number of distance and angle constraints per atom, respectively. For angle constraints, a further distinction can be made whether the relevant angle constraints refer to angles that all lie in one plane (trigonal coordination) or not (tetrahedral or higher coordination). The latter are referred to here as 3D angle constraints.

[0069] Accordingly, the "4 / 3-distance constraints" are called the number of distance degrees of freedom, the "5 / 3-angle constraints" are called the number of angular degrees of freedom, and the "5 / 3-3D angle constraints" are called the number of 3D angular degrees of freedom, each per atom (abbreviated as "pA").

[0070] In addition, the following considerations are made: The Makishima-Mackenzie model takes sums and averages with isotropic interactions. However, in the region of the boroxole ring, the interactions are not isotropic, and "weak" sliding is possible within the plane of the boroxole ring.

[0071] Taking this into account, the elastic modulus E can be considered as consisting of a shear part and a compression-expansion part, which is expressed by the following equation:See for example H. Foell, Skript zur Vorlesung “Einfuehrung in die Materialwissenschaft I“, Christian Albrechts-Universitaet Kiel, pp. 79 - 83:

number

[0072] where G is the shear modulus, K is the compression modulus, and μ is Poisson's ratio. Optionally, E can be calculated from one of the parameter pairs G and K, G and μ, and K and μ according to (11).

[0073] Here, the theory of Makishima and Mackenzie is modified in that the proportionality relationship between elastic modulus and dissociation energy density given above applies to the shear modulus G rather than the elastic modulus E:

number

[0074] For the shear modulus, no further proportionality to packing density is applied at this point, and the relationship to packing density shown here as well as in Makishima and Mackenzie is further introduced below.

[0075] The fact that the presence of boroxole rings leads to a reduction in the shear modulus of the sliding surface is taken into account by the prefactor f, which is defined as the ratio between the numbers. The first number is the angular constraint number pA reduced by (2 / 3) the difference between the number of 3D angular degrees of freedom pA and the number of angular degrees of freedom pA. The second number is the angular constraint number pA. If no boroxole rings are present, the prefactor is 1, and if boroxole rings are present, the prefactor is less than 1.

[0076]

number

[0077] The number (2 / 3) comes from the following considerations regarding shear: the boroxol rings are assumed to be distributed such that (1 / 3) lie in the plane perpendicular to the shear axis and (2 / 3) lie in the plane containing the shear axis. Only the latter two contribute to the reduction of the shear modulus. Therefore, also, if we do not count all the angular constraints, but only the 3D angular constraints, then only (2 / 3) of the angular degrees of freedom that arise further are counted.

[0078] In contrast to the shear modulus, the compressive modulus is not expected to change significantly due to the presence of sliding surfaces. For consistency reasons, this affects the Poisson's ratio μ. In this regard, (11d) is taken into account. If the introduction of sliding surfaces changes G and K does not change due to an otherwise unchanged ratio, this is equivalent to a change in μ Δμ f To quantify this change to a first approximation, K is expanded linearly in f and μ; in this case it is further required that ΔK=0 applies:

number

[0079] the result,

number

[0080] Since the glasses according to the invention are silicate glasses, quartz glass is chosen as the starting point for the development. For fused silica, μ=0.17 and f=1 apply, so these values ​​are inserted into the formula in square brackets. The formula therefore takes the value 0.2574. Δμ for other silicate glasses f To obtain −0.2574, −0.2574 is multiplied by Δf=f−1, where f is the value obtained from (13) for this other glass.

[0081] When changing from silica glass to other silicate glasses, there is another factor to consider regarding μ. Other silicate glasses have similar but different packing densities, and a positive correlation between μ and packing density applies: see Greaves, G., Greer, A., Lakes, R., Rouxel, T, Poisson's ratio and modern materials, Nature Mater 10, 823-837 (2011). This is due to the fact that Δμ χFor glasses according to the invention, this can be assumed to be linear, so the following applies:

number

[0082] The starting point is again quartz glass, for which χ = 0.33367062 is applied. In this case, Δ χ is calculated from the value of χ calculated according to (6) and 0.33367062 according to Δχ=χ-0.33367062. In the left denominator, μ=0.17, and in the right denominator, χ=0.33367062. Thus, μ of the glass according to the present invention is

number

[0083] The formula for E is written as this and (11b):

number

[0084] "a" and "b" are adjustable parameters. By evaluating a series of different silicate glasses (soda-lime glasses, borosilicate glasses, aluminosilicate glasses), the following formula is derived:

number

[0085] where:

number

number

[0086] Since the glass according to the present invention has a combination of the above-mentioned constituent phases, it is suitable to first numerically specify each constituent phase in order to calculate the number of distance constraints, angle constraints and 3D angle constraints per atom.

[0087] The following values ​​are firstly calculated according to the method described in DE 102014119594, where the number of angular constraints of all cations is calculated in particular as in DE 102014119594, but here only for boron and aluminum. Furthermore, the degree of ionization of the cation-oxygen compounds is not calculated according to formula (8) from DE 102014119594, but according to formula (3) from Alberto Garcia, Marvon Cohen, First Principles Ionicity Scales, Phys. Rev. B 1993. The coordination numbers required for this are taken from the mineralogy literature listed below in the discussion of the constituent phases; according to Conradt R. cited above, it is assumed that the coordination numbers of the cations in the glass are equal to the coordination numbers of the corresponding crystalline phases.

[0088] The following applies: [Table 8]

[0089] Therefore, the angular constraint b per atom of the completed glass W The calculation rules for finding are as follows:

number

[0090] Similarly, the 3D angular constraints per atom in the finished glass, b 3D-W The calculation rules for finding are as follows:

number

[0091] Similarly, the distance constraint b per atom of the completed glass A The calculation rules for finding are as follows:

number

[0092] In consideration of the thermal strengthening, the elastic modulus calculated according to formula (19) is preferably at least 71 GPa, preferably at least 72 GPa, particularly preferably at least 73 GPa, very preferably at least 74 GPa, and even more preferably at least 75 GPa. Preferably, the elastic modulus calculated according to formula (19) is in the range of 71 to 79 GPa, more preferably 72 to 78 GPa, more preferably 73 to 77 GPa, and even more preferably 74 to 76 GPa. For example, the elastic modulus calculated according to formula (19) may be at most 79 GPa, at most 78 GPa, at most 77 GPa, or at most 76 GPa.

[0093] Thermal expansion in glassy state (CTE liquid ) CTE liquid is the CTE Glas In addition to the usual thermal expansion coefficient described by, it includes a structural reorganization effect (see F. Mauch, JJ Jaeckle, cited above), which is assumed to be proportional, firstly, to the packing density and, secondly, to the elastic modulus. Firstly, the higher the packing density, the less space is available internally for reorganization, and the more the system must move outward to take up space if reorganization is required. Secondly, the higher the elastic modulus, the more the structure resists reorganization, and the more the system must move outward to take up space if reorganization is required.

[0094] Returning to equations (6) and (18), CTE liquid Apply:

number

[0095] χ etc. are calculated as above. "a" and "b" are adjustable parameters. By evaluating a series of different silicate glasses (soda-lime, borosilicate, aluminosilicate glasses), the following formula is derived:

number

[0096] In this way, the CTE liquid The average error when calculating is 2.3 ppm / K.

[0097] Taking into account the thermal strengthening, the CTE was calculated according to Eq. (24) liquid is preferably at least 22 ppm / K, more preferably at least 22.5 ppm / K, particularly preferably at least 23 ppm / K, very particularly preferably at least 23.5 ppm / K, in contrast more preferably at least 24 ppm / K, for example at least 24.5 ppm / K, at least 25 ppm / K, at least 25.5 ppm / K or at least 26 ppm / K. Preferably, the CTE calculated according to formula (24) liquid is in the range of 21 to 33 ppm / K, more preferably 21.5 to 32.5 ppm / K, even more preferably 22 to 32 ppm / K, even more preferably 22.5 to 31.5 ppm / K, even more preferably 23 to 31 ppm / K, even more preferably 23.5 to 30.5 ppm / K, even more preferably 24 to 30 ppm / K, even more preferably 24.5 to 291.5 ppm / K, even more preferably 25 to 29 ppm / K, even more preferably 25.5 to 28.5 ppm / K, even more preferably 26 to 28 ppm / K. For example, the CTE calculated according to the formula (24) liquid may be at most 33 ppm / K, at most 32.5 ppm / K, at most 32 ppm / K, at most 31.5 ppm / K, at most 31 ppm / K, at most 30.5 ppm / K, at most 30 ppm / K, at most 29.5 ppm / K, at most 29 ppm / K, at most 28.5 ppm / K, or at most 28 ppm / K.

[0098] Work Points Viscosity is 10 4The working point VA in dPa·s can be calculated by the average bond strength as well as the thermal expansion. It is known from the literature that the melting point of e.g. metals is inversely proportional to the bond energy (or "depth of the interatomic potential well"): see e.g. H. Foell, Skript zur Vorlesung "Einfuehrung in die Materialwissenschaft I", Christian Albrechts-Universitaet Kiel, pp. 79 - 83. Here, the melting point is assumed to be identical to the working temperature, although with some skepticism.

[0099] That is, the formula

number

number

[0100] In this way, the average error when calculating VA is 28K.

[0101] In view of the desired flat profile of the viscosity curve, the VA calculated according to formula (25) is preferably at least 1200 ° C, more preferably at least 1210 ° C, particularly preferably at least 1220 ° C, very preferably at least 1230 ° C, most preferably at least 1240 ° C. In view of process compatibility, the VA calculated according to formula (25) is preferably at most 1300 ° C, for example at most 1290 ° C, at most 1280 ° C, at most 1270 ° C, or at most 1260 ° C. Preferably, the working point VA calculated according to formula (25) is in the range of 1200 ° C to 1300 ° C, more preferably 1210 ° C to 1290 ° C, more preferably 1220 ° C to 1280 ° C, more preferably 1230 ° C to 1270 ° C, more preferably 1240 ° C to 1260 ° C.

[0102] Difference between working point and annealing point Considering the above-mentioned "shortness" and "length" of the glass, that is, the steepness or flatness of the viscosity curve at temperatures higher than the annealing point, the viscosity is set to 10 13 The difference between the working point VA, in dPa·s, and the annealing point OK is particularly important.

[0103] Surprisingly, it turns out that there is a relationship between this difference on the one hand and the number of angular degrees of freedom on the other hand, which allows not only a direct statement in terms of VA-OK but also an indirect determination of the annealing point via the relationship OK=VA-(VA-OK).

[0104] The following considerations provide a starting point: How far apart TG and OK are from each other is a question of the temperature profile of viscosity in the region of the supercooled melt. In a narrow temperature interval this can be described by the Arrhenius thermal activation model. For a description over the whole temperature range, more complex models are needed. The most common model is the Adam-Gibbs model: see G. Adam, JH Gibbs, On the Temperature Dependence of Cooperative Relaxation Properties in Glass-Forming Liquids, J. Chem. Phys. 43 (1965) pp. 139-145. It combines the Arrhenius thermal activation equation for the motion of a single atom with the consideration of how many atoms must interact to allow partial motion in a viscous fluid. The result is a relationship between viscosity and configurational entropy.

[0105] This relationship allows us to understand why there are "short" and "long" glasses and how this depends on the composition. As a rule of thumb, the higher the number of configurational degrees of freedom, the "shorter" the glass. The number of configurational degrees of freedom also depends on the composition, as already explained above. In glasses with a predominance of covalent bonds, such as between silicon and oxygen, this number is low. In glasses with a predominance of ionic bonds, such as between sodium and oxygen, this number is high.

[0106] A quantitative measure of the "shortness" of glasses that is well suited for deep physicochemical considerations is the concept of "fragility", which dates back to Austen Angell: see Charles Austen Angell, Thermodynamic aspects of the glass transition in liquids and plastic crystals, Pure & Appl. Chem. 63, No. 10 (1991), pp. 1387-1392.

[0107] This background suggested testing the relationship between the parameter VA-OK and the number of configurational degrees of freedom. Here we focus on the latter, since a real reconstruction always involves the use of angular degrees of freedom. In this case, the number of angular degrees of freedom per atom, f W is calculated from the angle-related constraint numbers as follows; see (20).

[0108]

number

[0109] Evaluating a series of different silicate glasses (soda-lime glasses, borosilicate glasses, aluminosilicate glasses) leads to the following formula:

number

[0110] OK can be calculated from VA and VA-OK. The average error of OK is 22K.

[0111] Taking into account the reinforcement properties, the OK calculated according to the formula (25, 27) is preferably at least 595 ° C, more preferably at least 600 ° C, particularly preferably at least 605 ° C, and most preferably at least 610 ° C. Taking into account the flat profile of the viscosity curve and the above VA values, the OK calculated in this way is preferably at most 650 ° C, for example at most 640 ° C, at most 630 ° C, or at most 620 ° C. Preferably, the annealing point OK calculated according to the formula (25, 27) is in the range of 595 ° C to 650 ° C, more preferably 600 ° C to 640 ° C, more preferably 605 ° C to 630 ° C, and even more preferably 610 ° C to 620 ° C.

[0112] Selection of appropriate constituent phases Leadmarginalite Reedmergnerite is an essential component of the glasses according to the invention, taking into account the desired flat profile of the viscosity curve and the resulting desired low number of angular degrees of freedom per atom. Reedmergnerite is composed of SiO4 and BO4 tetrahedra, i.e., tectosilicate. The sodium ions filling the framework are five-fold coordinated: see Appleman, DE, Clark, JR: Crystal structure of reedmergnerite, a boron albite, and its relation to feldspar crystal chemistry. Am. J. Sci. 50, 1827-1850 (1965). This allows for the desired high elastic modulus, as well as the CTE. liquid This is advantageous for the high packing density that is desired in view of the above.

[0113] The proportion of lead margnerite in the entire glass is in the range of 10 to 50 mol%, preferably 12 to 45 mol%, more preferably 15 to 42 mol%, more preferably 18 to 40 mol%, for example 18.5 to 28.5 mol%, or 30 to 40 mol%. For example, the amount of lead margnerite may be, for example, at least 10 mol%, at least 12 mol%, at least 15 mol%, at least 18 mol%, at least 18.5 mol%, or at least 30 mol%. The amount of lead margnerite may be, for example, at most 50 mol%, at most 45 mol%, at most 42 mol%, at most 40 mol%, or at most 28.5 mol%.

[0114] The CTE desired herein Glas The CTE of lead margnerite glass is higher than the maximum value of Glas Taking into account this, the proportion of leadmargnerite is up to 50 mol %. 1 mol of leadmargnerite means 1 mol of (Na2O·B2O3·6SiO2) / 8.

[0115] SiO 2 A desired flat profile of the viscosity curve and, consequently, a desired low number of angular degrees of freedom per atom as well as a desired low maximum CTE Glas Taking this into consideration, leadmargnerite is reasonably combined with pure SiO2 as a further constituent phase.

[0116] SiO2 glass, as it is commonly known, is a glass composed of SiO4 tetrahedra, i.e. a tectosilicate, but it is not "filled" and does not have the desired high elastic modulus, as well as the CTE. liquid Moreover, a too high proportion of SiO2 as a constituent phase leads to a too high working point of the glass from the viewpoint of processing technology.

[0117] The proportion of SiO2 glass in the entire glass is in the range of 10 to 60 mol%, preferably 20 to 55 mol%, more preferably 25 to 52 mol%, more preferably 30 to 50 mol%, more preferably 32 to 49 mol%, more preferably 33 to 47 mol%, for example 35 to 46 mol%. For example, the proportion of SiO2 glass may be at least 10 mol%, at least 20 mol%, at least 25 mol%, at least 30 mol%, at least 32 mol%, at least 33 mol%, or at least 35 mol%. For example, the proportion of SiO2 glass may be at most 60 mol%, at most 55 mol%, at most 52 mol%, at most 50 mol%, at most 49 mol%, at most 47 mol%, or at most 46 mol%.

[0118] Potassium-leadmargnellite To increase the resistance to devitrification, potassium analogues of leadmargnerite may be added to the glass. When such an admixture is used, the finished glass is more stable against devitrification since it contains potassium as well as sodium as an alkali metal. With regard to the number of angular degrees of freedom per atom, it behaves similarly to leadmargnerite. This base glass can be understood as a potassium analogue of leadmargnerite with the danburite structure, and henceforth will be called "potassium-leadmargnerite": see Mineralogical Magazine 57 (1993) 157-164.

[0119] The glass of the present invention may contain potassium-leadmargnellite in a ratio of 0 to 25 mol %. In consideration of devitrification resistance, a preferred embodiment contains at least 1 mol % potassium-leadmargnellite, particularly at least 2 mol % or at least 5 mol % potassium-leadmargnellite. One mole of potassium-leadmargnellite means one mole of (K2O·B2O3·6SiO2) / 8.

[0120] Preferably, the proportion of potassium-leedmargnerite in the glass according to the invention is in the range of 1 to 20 mol%, more preferably 2 to 19 mol%, more preferably 2.5 to 18.5 mol%, for example 3 to 17 mol%, or 4 to 16 mol%, or 5 to 15 mol%. For example, the proportion of potassium-leedmargnerite may be at least 1 mol%, at least 2 mol%, at least 2.5 mol%, at least 3 mol%, at least 4 mol%, or at least 5 mol%. For example, the proportion of potassium-leedmargnerite may be at most 20 mol%, at most 19 mol%, at most 18.5 mol%, at most 17 mol%, at most 16 mol%, or at most 15 mol%.

[0121] In a preferred embodiment, the proportion of leadmargnerite in the glass is greater than the proportion of potassium-leadmargnerite, in particular at least twice as much.

[0122] B 2 O 3 The proportion of diboron trioxide also provides a small number of angular degrees of freedom (not 3D angular degrees of freedom), albeit to a lesser extent than silicon dioxide, without affecting meltability. It can therefore be provided in a proportion of 0 mol% to 10 mol%. However, if the proportion of B2O3 is too high, the elastic modulus decreases. Preferably, the proportion of diboron trioxide is in the range of 0.5 to 8 mol%, more preferably 1 to 6 mol%, more preferably 1.5 to 5 mol%, for example 2 to 4.5 mol%. The amount of diboron trioxide may be, for example, at least 0.5 mol%, at least 1 mol%, at least 1.5 mol%, or at least 2 mol%. The proportion of diboron trioxide may be, for example, at most 10 mol%, at most 8 mol%, at most 6 mol%, at most 5 mol%, or at most 4.5 mol%.

[0123] Cordierite, Anorthite, Diopside Leadmargnerite and its potassium analogues are alkaline. Alkaline glasses, as mentioned above, have a high coefficient of expansion. SiO2 and B2O3 may be added to lower the coefficient of expansion, but their use is limited with regard to VA and modulus. Further phases may be added which contribute to shifting the coefficient of expansion to intermediate values, without the above-mentioned disadvantages of SiO2 and B2O3. These are the alkaline earth metal (alumino) silicates cordierite, anorthite and diopside. Anorthite and diopside are particularly preferred, and one of these two phases is always present in the glasses according to the invention.

[0124] 1 mole of cordierite means 1 mole of (2MgO·2Al2O3·5SiO2) / 9. The proportion of cordierite in the glass according to the invention is 0-10 mol%, preferably 0.1-8 mol%, more preferably 0.5-6 mol%, more preferably 0.9-4.1 mol%, for example 1.5-4 mol%. The proportion of cordierite may for example be at least 0.1 mol%, at least 0.5 mol%, at least 0.9 mol% or at least 1.5 mol%. The proportion of cordierite may for example be at most 10 mol%, at most 8 mol%, at most 6 mol%, at most 4.1 mol% or at most 4 mol%.

[0125] 1 mole of anorthite means 1 mole of (CaO·Al2O3·2SiO2) / 4. The proportion of anorthite in the glass according to the invention is 0-15 mol%, preferably 1-12 mol%, further preferably 1.5-10 mol%, for example 2-9 mol%, or 3-8 mol%. The proportion of anorthite may for example be at least 1 mol%, at least 1.5 mol%, at least 2 mol%, or at least 3 mol%. The proportion of anorthite may for example be at most 15 mol%, at most 12 mol%, at most 10 mol%, at most 9 mol%, or at most 8 mol%.

[0126] 1 mole of diopside means 1 mole of (MgO·CaO·2SiO2) / 4. The proportion of diopside in the glass according to the invention is 0-15 mol%, preferably 1-12 mol%, more preferably 2-10 mol%, for example 3-8 mol%. The proportion of diopside may be, for example, at least 1 mol%, at least 2 mol% or at least 3 mol%. The proportion of diopside may be, for example, at most 15 mol%, at most 12 mol%, at most 10 mol% or at most 8 mol%.

[0127] According to the invention, the sum of the proportions of anorthite and diopside in the glass according to the invention is in the range of 1 to 30 mol%, preferably 2 to 25 mol%, more preferably 5 to 20 mol%, more preferably 6 to 19 mol%, more preferably 7 to 18 mol%, more preferably 8.5 to 17 mol%, more preferably 10 to 16 mol%. For example, the sum of the proportions of anorthite and diopside may be at least 1 mol%, at least 2 mol%, at least 5 mol%, at least 6 mol%, at least 7 mol%, at least 8.5 mol%, or at least 10 mol%. For example, the sum of the proportions of anorthite and diopside may be at most 30 mol%, at most 25 mol%, at most 20 mol%, at most 19 mol%, at most 18 mol%, at most 17 mol%, or at most 16 mol%.

[0128] Further ingredients In addition to the components already mentioned, the glass may contain further components, referred to herein as "residue". The proportion of the residue in the glass according to the invention is advantageously at most 5 mol %, in order not to interfere with the glass properties adjusted by careful selection of the appropriate base glass. In particularly preferred embodiments, the amount of residue in the glass is at most 3 mol %, more preferably at most 2 mol %, or at most 1 mol %, or at most 0.5 mol %. In particular, the residue comprises oxides that are not contained in the base glass described herein. Thus, in particular, the residue does not comprise SiO2, Al2O3, B2O3, MgO, CaO, Na2O or K2O.

[0129] When it is stated herein that a glass is free of an ingredient or phase or free of a particular ingredient or phase, it means that this ingredient or phase may possibly be present in the glass as an impurity. That is, it is not added in a substantial amount. According to the present invention, an insubstantial amount is less than 300 ppm (mol), preferably less than 100 ppm (mol), particularly preferably less than 50 ppm (mol), and most preferably less than 10 ppm (mol). In particular, the glass of the present invention is free of lithium, zinc, barium, zirconium, lead, arsenic, antimony, tin, bismuth and / or cadmium.

[0130] Preferred Glass Compositions A preferred embodiment is within the scope of the above base system, CTE Glas , C.T.E. liquid , resulting from setting the desired values ​​of elastic modulus, density, working point and anneal point.

[0131] Preferred compositions are characterized in that they have the following glass constituent phases: [Table 9]

[0132] Highly preferred compositions are characterized in that they have the following glass constituent phases: [Table 10]

[0133] manufacturing According to the present invention there is also provided a method for producing the glass of the present invention comprising the steps of: - melting glass raw materials; - optionally forming a glass article from the molten glass, in particular a glass tube, a glass ribbon or a glass sheet, - The process of cooling the glass.

[0134] The glass according to the invention can be melted, for example, in industrial glass melters, both with air-fuel (air combustion) and oxygen-fuel (oxyfuel) or fully electrically. All usual chemical and physical fining methods are suitable for removing residual gas bubbles. However, fining with alkali halides is preferred, advantageously with NaCl or KCl, particularly preferably with NaCl. Here, alkali halide salts may be added in amounts of, for example, 0.5 to 2.5% by weight.

[0135] The glass body according to the invention is advantageously used as a glass sheet or glass plate. The glass body can be produced by the float process, which is particularly preferred according to the invention. The shaping of the glass body according to the invention can also be carried out by other processes known for the production of flat glass, such as various drawing processes (e.g. updraw, downdraw, overflow fusion, Foucault process), casting or rolling processes.

[0136] The stress relief / cooling of the glass bodies according to the invention is preferably carried out in a continuously operated roller cooling furnace, which may be electrically or gas heated. The glass bodies according to the invention are then preferably subjected to low thermal stresses (preferably <2 N / mm 2 ) only.

[0137] The method according to the invention may further comprise a step of cold working the glass. The glass body according to the invention can be made into any desired shape by cutting and edge grinding, for example for fire-resistant glazing, furnace windows for pyrolysis ovens, microwave covers, cooking surfaces for kitchen ranges or curved windscreens for vehicles.

[0138] The method according to the invention may also include a step of thermal strengthening. For example, the glass according to the invention may be subjected to a thermal strengthening process after the melting process, the forming process, the stress relief / cooling process and the cold post-treatment process. In this case, the glass body according to the invention, for example a glass sheet, is guided, preferably lying or suspended, into the device and is heated to a transition temperature T G The glass body is then rapidly heated to a temperature of up to 150 °C above the surface temperature. The glass body is then rapidly cooled, for example by blowing cold air onto it via a nozzle system. As a result of the rapid cooling of the glass surfaces, they are frozen in an extended grid, while the interior of the glass body cools more slowly and has time to contract more strongly. As a result, compressive stresses are generated in the surface layers and tensile stresses in the interior of the glass body. The magnitude of the compressive prestress in this case is determined by the CTE Glas , C.T.E. liquid The temperature depends on various glass parameters such as annealing point, softening point, elastic modulus, etc., and also on the amount of heat transfer between the cooling medium and the glass surface and the thickness of the glass body. Usually, a compressive prestress of at least 120 MPa is set as a target. As a result, the bending strength of the glass body can be doubled to tripled compared to non-strengthened glass. According to the invention, preferably, the glass is heated to a temperature of 700-750°C and blown at a blowing pressure of 1-16 kPa to a temperature of 300-550 W / m 2 The glass according to the invention is tempered in cold air at a heat transfer coefficient of 100 K. In the glass according to the invention, compressive prestress values ​​of 120-160 MPa are preferably achieved in a commercially available air prestressing device.

[0139] Applications and Glassware The invention also relates to the use of the glass bodies according to the invention as fire-resistant safety glass, as sight glasses in pyrolysis furnaces, as cover plates in microwave ovens, as cooking surfaces in domestic appliances, as sight glasses in vehicle glazing, as high-strength and chemically resistant pressure glazing (Maxos glass) and as bulletproof windows in vehicles and buildings (bulletproof glass).

[0140] In addition to glass, the present invention also provides glass articles formed from glass, such as plates, particularly having a thickness in the range of 4 to 12 mm.

[0141] The glasses of the present invention can be particularly well heat strengthened. The present invention therefore relates to both heat strengthenable and heat strengthened glass articles.

[0142] Favorable characteristics The glass and / or glass article of the present invention preferably complies with DIN EN 1748-1.

[0143] Preferably, safety glass properties according to DIN EN 13024-1 are provided (four-point bending strength min. 120 MPa, 50 x 50 mm 2 At least 40 fragments (d = 4-12 mm). At thickness d = 6 mm, 50 x 50 mm 2 The number of fragments in is preferably in the range of 50 to 180, more preferably in the range of 60 to 150, even more preferably in the range of 70 to 130, and even more preferably in the range of 80 to 120.

[0144] The fire resistance time according to DIN 4102 / ISO 834 for d=6 mm is preferably at least 120 minutes (G90) according to ETK, more preferably at least 120 minutes, even more preferably at least 180 minutes.

[0145] Preferably, the rupture temperature in the fire test according to the standard temperature curve ETK for d=6 mm is in the range of 1030°C to 1130°C, for example 1040°C to 1120°C, 1050°C to 1110°C or 1070°C to 1100°C. It is preferably confirmed according to EN 1363. The rupture temperature in the fire test according to the standard temperature curve ETK for d=6 mm can be, for example, at least 1030°C, at least 1040°C, at least 1050°C or at least 1070°C. The rupture temperature in the fire test according to the standard temperature curve ETK for d=6 mm can be, for example, at most 1130°C, at most 1120°C, at most 1110°C or at most 1100°C.

[0146] Preferably, the above properties include a maximum temperature of 750° C. and a heat transfer coefficient of up to 500 W / m 2 This can be achieved in conventional air prestressing equipment (radiation or convection) for K soda-lime glass, i.e. the properties are particularly relevant for the thermally toughenable glass articles of the present invention.

[0147] Preferably, the surface compressive stress (CS) of the strengthened glass article of the present invention is in the range of 100 to 160 MPa, more preferably 110 to 150 MPa, and even more preferably 120 to 140 MPa. For example, the surface compressive stress (CS) of the strengthened glass article of the present invention may be at least 100 MPa, at least 110 MPa, or at least 120 MPa. For example, the surface compressive stress (CS) of the strengthened glass article of the present invention may be at most 160 MPa, at most 150 MPa, or at most 140 MPa.

[0148] Preferably, the four-point bending strength of the tempered glass article of the present invention is in the range of 160 to 220 MPa, more preferably 170 to 210 MPa, and even more preferably 180 to 200 MPa. Preferably, the four-point bending strength is determined in accordance with EN1288-3. For example, the four-point bending strength of the tempered glass article of the present invention may be at least 160 MPa, at least 170 MPa, or at least 180 MPa. For example, the four-point bending strength of the tempered glass article of the present invention may be at most 220 MPa, at most 210 MPa, or at most 200 MPa.

[0149] Working Example Comparative Example Glass compositions not according to the invention will first be described below, which are not included in the base system according to the invention or do not meet the conditions regarding the proportions of the constituent phases.

[0150] In the table below, first, the oxide compositions (mol % on an oxide basis) of Comparative Examples V1 to V8 are shown.

[0151] [Table 11]

[0152] The conversion to the constituent phases results in the compositions (mol %) of the exemplary glasses V1 to V8 shown in the table below.

[0153] [Table 12]

[0154] In comparative examples V3 and V5-V8, the proportions of the constituent phases do not add up to 100 mol % because these glasses contain oxides that are not included in the base glasses described herein and thus represent "residuals".

[0155] Comparative examples V1 to V5 and V8 contain negative phase proportions and are therefore not part of the base system according to the invention. In V6, the proportion of leadmargnerite and the proportion of diboron trioxide are too high, while the proportion of silicon dioxide is too low. In contrast, in V7, the proportion of cordierite and the proportion of anorthite are too high and the proportion of leadmargnerite is too low.

[0156] The following table shows the oxide compositions (mol % on an oxide basis) of Comparative Examples V9 to V16, which are also not according to the present invention.

[0157] [Table 13]

[0158] The conversion to the constituent phases results in the compositions (mol %) of the exemplary glasses V9 to V16 shown in the table below.

[0159] [Table 14]

[0160] In comparative examples V9, V10, V13 and V14, the percentages of the constituent phases do not add up to 100 mol % because these glasses contain oxides that are not included in the base glasses described herein and thus represent "residuals".

[0161] Comparative examples V10 to V16 contain negative phase proportions and are therefore not part of the base system according to the invention. In V9 the anorthite proportion is too high and the leadmargnerite proportion is too low.

[0162] Examples of the present invention The following exemplary glasses are examples of the present invention in accordance with the present invention.

[0163] In the table below, the compositions of Examples A1 to A8 according to the present invention are shown first in terms of constituent phases (mol %).

[0164] [Table 15]

[0165] The following table shows the compositions of further examples A9 to A11 according to the invention in terms of constituent phases (mol %).

[0166] [Table 16]

[0167] As described above, various characteristic values ​​can be calculated from the glass composition of the constituent phases. The following table shows the density ρ calculated according to formula (5), the thermal expansion coefficient CTE calculated according to formula (4) for Examples A1 to A11 according to the present invention. Glas , the CTE calculated according to equation (24) liquid , the elastic modulus E calculated according to equation (19), the working point VA calculated according to equation (25), and the annealing point OK calculated according to equations (25, 27).

[0168] [Table 17]

[0169] In other words, by appropriately selecting the constituent phases, the density, thermal expansion coefficient (CTE) Glas , C.T.E. liquid We have succeeded in obtaining glasses with advantageous properties in terms of elastic modulus E, working point VA, and annealing point OK.

[0170] Strengthening and fire testing Various glass compositions were melted in 1 liter crucibles on a laboratory scale and their properties were measured. Selected glass compositions were melted on a small scale (10 liter crucibles), transferred to a manual rolling plant at a temperature of about 1300°C, formed into flat glass bodies with a glass thickness of about 6 mm between two water-cooled rollers, slowly stress-relieved and cooled to room temperature. The resulting flat glass bodies were 350 × 150 mm 2The glass was then processed (cut and edge grinded) to the desired size and thermally strengthened using a commercially available air prestressing device. The thermally strengthened glass bodies were checked for compressive prestress, bending strength, and appearance of the broken pieces. The selected thermally strengthened glass bodies were subjected to fire tests in a small fire test furnace.

[0171] The results for comparative examples V11, V1 and V4 and for examples A1, A7, A8, A10 according to the invention are given in the two tables below.

[0172] The following table shows the confirmed compressive stress (MPa), confirmed bending strength (MPa) and 50×50 mm 2 The number of identified fragments was determined in accordance with DIN EN 13024-1.

[0173] [Table 18]

[0174] It can be seen that the glass according to the invention has a higher compressive stress, a higher bending strength and a higher number of fragments compared to the comparative example after thermal strengthening. The glass according to the invention is therefore characterized by improved properties compared to the comparative example.

[0175] The fire test results are shown in the table below.

[0176] [Table 19]

[0177] It can be seen that the glass according to the invention gives better results in the fire test compared to the comparative example. The glass according to the invention can withstand higher temperatures for a longer time. Thus, compared to the comparative example, the glass according to the invention is not only distinguished by improved safety properties, but also by improved fire resistance properties. The glass according to the invention is therefore particularly well suited for fire-resistant and safety glazing, in particular fire-resistant safety glass.

Claims

1. A glass comprising the following phases: 【Table 1】 1. A glass having a composition comprising:

2. The following phases constitute the glass: 【Table 2】 2. The glass of claim 1 having

3. 3. The glass according to claim 1, wherein the proportion of leadmargnerite is in the range of 15 to 42 mol %.

4. 4. The glass according to claim 1, wherein the proportion of potassium leadmargnerite is in the range from 2 to 19 mol %.

5. 5. The glass according to claim 1, wherein the proportion of silicon dioxide is in the range from 25 to 52 mol-%.

6. 6. The glass according to claim 1, wherein the proportion of diboron trioxide is in the range from 1 to 6 mol %.

7. The following phases constitute the glass: 【Table 3】 7. The glass according to claim 1, characterized in that it has

8. The following formula (4) [0010] The CTE was calculated according to Glas The glass of any one of claims 1 to 7, wherein the solubility is in the range of 3.8 to 4.8 ppm / K.

9. The following formula (5) [0025] The density calculated according to is 2.25 to 2.45 g / cm 3 9. The glass of claim 1, wherein the viscosity is in the range of

10. The following formula (19) [0030] The glass according to any one of claims 1 to 9, having an elastic modulus calculated according to the formula: in the range of 71 to 79 GPa.

11. The following formula (24) [0045] The CTE was calculated according to liquid The glass of any one of claims 1 to 10, wherein the solubility is in the range of 21 to 33 ppm / K.

12. The following formula (24) [0050] The CTE was calculated according to liquid and the following equation (4): [006] The CTE was calculated according to Glas The glass of any one of claims 1 to 11, wherein the ratio of

13. The following formula (25) [0070] The glass according to any one of claims 1 to 12, wherein the working point VA calculated according to is in the range of 1200°C to 1300°C.

14. The following equations (25, 27) [0080] [0090] The glass according to any one of claims 1 to 13, wherein the annealing point OK calculated according to is in the range of 595°C to 650°C.

15. The glass of claim 1, wherein the sum of the proportions of anorthite and diopside is 10 mol % or more.

16. The glass of claim 1, wherein the proportion of potassium leadmarginellite is 1 mol % or more.

17. The glass of claim 1, wherein the proportion of diboron trioxide is less than 4.84 mole percent.

18. A glass article from the glass according to any one of claims 1 to 17 in the form of a plate having a thickness of 4 to 12 mm.

19. 19. The glass article of claim 18, wherein the glass article is thermally strengthened and has a surface compressive stress (CS) in the range of 100-160 MPa.

20. 20. The glass article of claim 19, wherein the article has a four-point flexural strength in the range of 160 to 220 MPa.

21. 21. Use of the glass according to any one of claims 1 to 17 or the glass article according to any one of claims 18 to 20 as fire-resistant safety glass, as sight glass in pyrolysis furnaces, as cover plates for microwave ovens, as cooking surfaces in domestic appliances, as sight glass in vehicle glazing and / or as bulletproof windows (bulletproof glass) in vehicles and / or buildings.

22. A method for producing the glass of any one of claims 1 to 17, comprising the steps of: - melting glass raw materials; - optionally forming glass articles from the molten glass, in particular glass tubes, glass ribbons or glass sheets; - Cooling the glass The method comprising:

Citation Information

Patent Citations

  • Low-expansion heat-resisting fire-retardant glass

    CN1803683A

  • Photoconductive optical fiber for transmitting signal consisting of multicomponent glass with adjusted between coreewire and coating coefficient of expansion

    JP1977135322A

  • High chemical resisting and high heat resisting borosilicate glass capable of forming seal with tungsten

    JP1994199540A

  • Milky glass

    JP1994321573A

  • Fire prevention safe plate glass

    JP1995069669A